1997
DOI: 10.1074/jbc.272.10.6490
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Carrier Protein-2 Overexpression Enhances Sterol Cycling and Inhibits Cholesterol Ester Synthesis and High Density Lipoprotein Cholesterol Secretion

Abstract: Recent data indicate that sterol carrier protein-2 (SCP-2) functions in the rapid movement of newly synthesized cholesterol to the plasma membrane (Puglielli, L., Rigotti, A., Greco, A. V., Santos, M. J., and Nervi, F. (1995) J. Biol. Chem. 270, 18723-18726). In order to further characterize the cellular function of SCP-2, we transfected McA-RH7777 rat hepatoma cells with a pre-SCP-2 cDNA expression construct. In stable transfectants, pre-SCP-2 processing resulted in an 8-fold increase in peroxisomal levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
67
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 80 publications
12
67
0
Order By: Relevance
“…We hypothesize that the triggering event involved in the multiple effects of hepatic SCP-2 overexpression on lipid metabolism in mice was the increased FA and cholesterol cycling and intracellular cholesterol and phosphatidylcholine redistribution. This possibility is consistent with the results of previous studies in SCP-2-transfected cultured rat hepatoma cells (23) and in the whole animal (26). It was apparent that the velocity of the bidirectional flux of cholesterol and phosphatidylcholine between endoplasmic reticulum and plasma membranes was critically dependent upon SCP-2 expression levels.…”
Section: Figsupporting
confidence: 82%
See 1 more Smart Citation
“…We hypothesize that the triggering event involved in the multiple effects of hepatic SCP-2 overexpression on lipid metabolism in mice was the increased FA and cholesterol cycling and intracellular cholesterol and phosphatidylcholine redistribution. This possibility is consistent with the results of previous studies in SCP-2-transfected cultured rat hepatoma cells (23) and in the whole animal (26). It was apparent that the velocity of the bidirectional flux of cholesterol and phosphatidylcholine between endoplasmic reticulum and plasma membranes was critically dependent upon SCP-2 expression levels.…”
Section: Figsupporting
confidence: 82%
“…Experiments in cultured cell systems transfected with cDNAs encoding for the SCP-2/sterol carrier protein X (SCP-X) products demonstrated the role of these proteins in microsomal membrane utilization of FA for phospholipids, triglyceride, and cholesterol ester synthesis (19)(20)(21)(22). Overexpression of SCP-2 in rat hepatoma cells enhanced intracellular cholesterol cycling, increased plasma membrane cholesterol content, and inhibited cholesterol esterification and HDL production (23). In addition, studies in mice with disruption of the SCP-2/SCP-X gene have shown a failure in the oxidation of 2-methyl-branched FA and the side chain of cholesterol.…”
mentioning
confidence: 99%
“…The physiological impact of cholesterol binding proteins such as SCP-2 and L-FABP on cholesterol uptake, esterification, and excretion into bile was confirmed by studies with SCP-2 transgenic (i.e. overexpressing or antisense cDNA treated) mice and rats (177-179) Studies with radiolabeled cholesterol were consistent with many of the findings shown with the fluorescent DHE and other sterols in cultured cells (43,45,172,(190)(191)(192)(193)(194)(195)(196)(197). In one study, it was shown that overexpression of L-FABP in L-cell fibroblasts enhanced the transfer or radiolabled cholesterol from the plasma membrane to the endoplasmic reticulum for esterification (194).…”
Section: Physiological Significance Of In Vitro Studies With Dhe and mentioning
confidence: 77%
“…of Medicine, Clinical Nutrition Research Unit, Section of Gastroenterology, Univ. of Chicago, Chicago, IL), were maintained as described (27). For indirect immunofluorescence (see below), cells were grown on glass cover slip chambers and prepared as described earlier (28).…”
Section: Cell Culturementioning
confidence: 99%